Employee Management System and Customer Relation on Business Performance of Etos National Company - Fatchun Hasyim; Nanang Adie Setyawan; Marcellino Prima Diasta (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2023)
This study aims to prove and analyze the effect of the employee management system and customer relations on business performance at the outsourcing company Etos National Company. The population in this study are cleaning service employees who work under PT Etos Nasional. The number of samples was 67, using the purposive sampling technique. This study uses a quantitative approach, and literature study, interviews, and questionnaires carry out data collection methods. The scale used is a semantic differential scale. The analysis method used is descriptive analysis, validity test, reliability test, classical assumption test, multiple regression analysis, and hypothesis testing. The tool used in data processing is the SPSS application. Based on the test results, the regression equation is Y = 7,133 + 0,482 + 0,282 it can be concluded that the variable employee management system (X1) and customer relations (X2) have a positive and significant effect on business performance (Y).